DEVELOPMENT OF CADASTRAL MAPS AND PLANS IN THE GEOINFORMATION SYSTEM - K.R.Khakimova; A.Y.Rasulov; A.M.Abdumukhtorov; X.X.Ne’matov (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, three subsystems can be distinguished in the structure of the automated system of cadastral cartography: photogrammetric subsystem; subsystem of vector mapping and orthophotoplans; Let’s get acquainted with the processing of digital cartographic data.